Pengaruh leksika dan gramatika bahasa Rusia terhadap pembentukan karakter penuturnya - Machdalena, Susi; Ismail, Nany; Koeshandoyo, Eko Wahyu; Mariamurti, Prima Agustina; Wildan, Rahmi Imanda (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
This study aimed to analyze the influence of Russian vocabulary and grammar on the formation of the personalities of its speakers. In the Russian context, vocabulary and grammar play an important role in establishing communication patterns and the cultural identity of its speakers. This study used the qualitative descriptive method. The data were classified based on cultural data and vocabulary contained in anecdotes, phraseologies, folklore, the pronominal use of vy ‘you' and ty 'you', the formation of atroponyms using suffixes, the use of exclamation marks, and the use of numbers. The results of this study show that stereotypes, phraseologies, folklore, vy ‘you' and ty 'you' pronouns, anthroponic suffixes, interjections, and the use of numbers can shape the character of speakers. All these elements affect how words, grammar, and sentence structure are used in Russian. In addition, it can affect the characteristics of the speaker, including attitudes, values, and thinking patterns. This research can provide a deeper understanding of how language plays an important role in shaping an individual's personality in a Russian linguistic context, as well as its implications for understanding the culture and identity of Russian-speaking peoples.